Determinants of financial distress: evidence from listed PN17 companies in Bursa Malaysia / Hafizah Mohd Jupri - Mohd Jupri, Hafizah (Faculty of Business Management, 2017)
Majority of the researchers used formulas and existed models in order to measure the financial distress of the firm. However, small number of them find out how financial performance of firms can be affected by financial distress. This study will investigate the impact of financial distress on financial performance towards the listed companies in PN17 by using financial ratios as the indicator. Hence, a panel data analysis of 16 listed Practice Note 17 companies in Bursa Malaysia from 2011 to 2015 periods (5 years) has been used in this study. This study uses five financial ratios as independent variables which are debt ratio, working capital turnover, total assets turnover, current ratio and quick ratio. The dependent variables of this study is return on assets. Panel regression analysis was used to recognize the most optimal financial ratios towards the return on assets. The findings of this paper designate that the working capital turnover and total assets turnover is the two variables that significantly show a negative and positive relationship with return on assets respectively. This paper argues that debt ratio, current ratio and quick ratio are less important in determining the return on assets in the financial performance of the financial distress’s firms.